AB0749 ARE THERE ANY DIFFERENCES IN THE EFFECTIVITY AND SAFETY OF CERTOLIZUMAB PEGOL IN PATIENTS WITH PSORIATIC ARTHRITIS ACCORDING THEIR GENDER?. (June 2019) - García, Rosa; Fernandez-Prada, Manuel; Conesa, Arantxa; Esteban, Jose Campos; Urruticoechea-Arana, Ana; Olive, Alejandro; Paredes, Silvia; Taverner, Delia; Gonzalez, Carlos; ,
Abstract : Background: Gender-related biochemical, hormonal and psychological factors could play an important role in the response to TNF blocker therapy in psoriatic arthritis (PsA). Scarce data are available analyzing differences in effectiveness and safety of the antiTNFs, and none in particular with Certolizumab Pegol (CZP) according to the gender. Objectives: To evaluate the influence of the gender in the effectiveness and safety of CZP in the routine clinical setting in PsA patients. Methods: Observational, national and muticentric cohort (approved by local ethical committee), PsA patients treated with CZP according to routine clinical practice were studied for 12 months. Clinical and disease characteristics and disease activity between gender were compared. Safety analysis: adverse events and withdrawn. Results: 347 PsA patients were analyzed. No statistical differences were found between women and men at baseline in demographics, clinical variables, except for previous biologic treatment and ESR (Table 1 ). In both genders, a statistical significant decreased was observed after 1 year of CZP treatment in the following variables: DAS28(CRP); SJC; TJC; PGA (patient global ssesment);% patients with enthesitis, dactilytis and nail disease; but with no differences between females and males. Variables that influence the response at 12 months are: disease duration, CRP and TJC at baseline. Drug survival of CZP was 80.1%, and no differences were observed in gender. Adverse events related to CZP were observed in 9.5% and 19.9% withdrawn treatment: 12.4% due to lack of effectiveness, 4.0% due to intolerance and 3.5% other reasons. Conclusion: CZP has shown to be effective and safe in PsA patient after a year of treatment in clinical practice regardless patient's gender. Disclosure of interests: Rosa García : None declared, Manuel Fernandez-Prada: None declared, arantxa Conesa: None declared, Jose Campos Esteban: None declared, aNA URRUTICOECHEA-ARANA: None declared, alejandro Olive: None declared, SILVIA PAREDES Speakers bureau: Bristol, Roche, amgen, Pfiser, abbvie, lilly, UCB, Delia Taverner Speakers bureau: amgen, pfiser, Bristol, Lilly, Roche, Carlos Gonzalez Consultant for: Celgene, Gilead, Janssen, Merk, Novartis, Pfizer, Speakers bureau: Celgene, Roche, UCB